(NhUDOVNIK NA[IH DNEJ n(B.(Nq(B.(NmQSKOWSKIJ(B.s (NMONOGRAFIQs - (Na(B.(NiKONNIKOWs ((NmOSKWAs (NmUZYKAs, 1966)
(NoNA I OPREDELILA W KONE^NOM S^ETE OSNOWNU@ IDE@ KNIGI (B,(NPERWONA^ALXNO ZADUMANNAQ TEMA (B"(NsIMFONI^ESKOE TWOR^ESTWO mQSKOWSKOGO(B" (NSTALA TEMNOJ (B" (NhUDOVNIK NA[IH DNEJ(B".s
Keywords: (NMONOGRAFIQs